التوجيه اللغوي لانفرادات الإمام نافع في القراءة - سلطاني, عمار (University of eloued جامعة الوادي, 2021)
هذه الدراسة الموسومة بالتوجيه اللغوي لانفرادات الإمام نافع رحمه الله في القراءة تعتبر عينية تناولت التوجيهات اللغوية للقراءات والأحرف التي انفرد بها الإمام نافع عن بقية القراء وبيانها من جانب الصوت والصرف والنحو بالإضافة إلى الإحاطة بالمعاني الواردة في كتب التفسير، ولقد ضمت الدراسة فصلين يتصدرهما تمهيد ومقدمة ففي الفصل الأول تناولت فيه ثلاث مباحث ماهية القراءات القرآنية، التوجيه اللغوي، والتعريف بالإمام نافع ثم فصل تطبيقي خصصناه للحديث عن التوجيه اللغوي لبعض ما انفرد به الإمام نافع من الحروف والقراءة وقد ضم ثلاث مباحث توجيه صوتي، وصرفي، ونحوي ثم خاتمة متبوعة بقائمة المصادر والمراجع وفهرس المحتويات.This study, which is tagged with the linguistic guidance for the singularities of Imam Nafi’, may God have mercy on him, in reciting, is considered in kind. It dealt with the linguistic directives of the readings and letters that Imam Nafi’ was unique to the rest of the readers and their statement from the side of sound, morphology and grammar, in addition to taking note of the meanings contained in the books of interpretation, and the study included two chapters headed by a preface and an introduction in The first chapter dealt with three sections on the nature of the Qur’anic readings, linguistic guidance, and the introduction of Imam Nafi’, then an applied chapter that we devoted to talking about linguistic guidance for some of what Imam Nafi’ was unique in of letters and reading. Contents.
لغة ودراسات
Keywords: التوجيه اللغوي- لانفرادات - الإمام نافع في القراءة; Orientation linguistique - pour les célibataires - Imam Nafie en lecture